Evaluación de selectividad de la mezcla herbicida nicosulfuron + atrazina en diferentes etapas de desarrollo en el cultivo de maíz - Vera Vera, Enoc Saúl (2016)
VIII. SUMMARY This research was conducted on the grounds of Mr. Enoch Vera Manobanda, located in the parish Caracol via Barreiro; with geographical coordinates of 79 ° 34'de west longitude and 01 ° 34' south latitude and a height of 32 m.s.n.m. The area has a humid tropical climate with an average annual temperature of 25.60 0C, an average annual rainfall of 1925.4 mm, relative humidity of 83% and 998.2 hours heliophany annual average. The soil is alluvial loam - clay, flat topography and regulate drainage. This work was performed in order to evaluate the selectivity of the mixture of the herbicides atrazine Nicosulfuron + at different stages of development of maize. As genetic material, seed of hybrid corn "Dekalb 7088", distributed by the company Ecuaquímica was used. Subtratamientos treatments and were made by mixing the Nicosulfuron + Atrazine in several doses (45 g / ha + 1.0 kg / ha, 45 g / ha + 1.5 kg / ha, 50 g / ha + 1.0 kg / ha, 50 g / ha + 1,5 kg / ha, 55 g / ha + 1,0 kg / ha, 55 g / ha + 1,5 kg / ha) at different times of application (20, 25, 30, 35 and 40 days after planting). experimental design "Divided Plots" Five subtratamientos and three replications with six treatments. The comparison of averages was performed by Tukey test at 95% probability. All agricultural practices that requires growing corn for normal development, such as land preparation, planting, weed control, irrigation, fertilization, control insect pests, diseases and harvesting were performed. To estimate the effects of treatments and subtratamientos, the selectivity of the herbicide at 7 and 14 days, weed control at 14 and 21 days, plant height, days to flowering, length and ear diameter, number evaluated of grains per ear, 1000 grain weight, yield and economic analysis. From the results it was determined that herbicide mixture Nicosulfuron + atrazine applied at different stages of development were selective in maize; toxicity caused by the herbicide to the crop in the first evaluation was little damage, disappearing after 14 days; the best weed control at 14 and 21 days was carried out with the mixture nicosulfuron + atrazine in doses of 45 g / ha + 1.5 kg / ha applied at 20 days after sowing; the greater plant height, length and ear diameter was achieved with the application of nicosulfuron + atrazine at doses of 45 g / ha + 1,0 kg / ha; variable number of grain and grain weight of 1000 reported better results using mixtures nicosulfuron + atrazine at doses of 45 g / ha + 1,0 kg / ha at 25 days after planting and the highest grain yield was observed with the mixture of nicosulfuron + atrazine at doses of 45 g / ha + 1,0 kg / ha applied at 25 days after planting and the highest net profit to $ 761.26